Potential contribution of SFL to task-based research: An examination of planning effects using genre-based theme analysis. (February 2022) - Qin, Jie
Abstract: The present study aims to investigate, within the framework of Systemic Functional Linguistics (SFL), the influence of pre-task planning on textual cohesion and generic coherence, as well as the potential contribution of SFL to task-based research with a focus on oral tasks. Fifty-six Chinese EFL learners retold the Modern Times episode under either 10-min strategic planning or no planning condition. Their oral production was collected and analyzed in terms of the narrative genre, types of themes, theme markedness, and thematic progression patterns. Whereas an SFL-based qualitative analysis seemed to suggest the use of more diverse lexico-grammatical resources for meaning-making and a more logical pattern of theme-rheme development among the planned learners, such results were not supported by the quantitative data, which displayed a more complex picture. It is also suggested that the functional, meaning-oriented perspective, by providing in-depth, qualitative description of speakers' deployment of discourse-semantic and lexico-grammatical resources, could complement and extend the structural and formal assessment of L2 task performance and development. Overall, this research provides novel evidence concerning the relationship between planning time and discourse management, as well as valuable insights into the potential contribution of SFL to task-based research.